Respuesta :

Step-by-step explanation:

2x - 5 = y - 5

2x = y

x = y/2

y - 3 = x + 1

Substitute the value of x here,

y - 3 = [tex]\rm{\dfrac{y}{2} + 1}[/tex]

y - 3 = [tex]\rm{\dfrac{y + 2}{2}}[/tex]

2y - 6 = y + 2

y = 8

Now, x = 8/2

x = 4

So, go for D part, it is the correct answer.

Good Night/Day !

Answer:

x = 4, y = 8

Step-by-step explanation:

For the triangles to be congruent by the HL theorem

Then the hypotenuse and legs must be congruent , that is

x + 1 = y - 3 → (1)

2x - 5 = y - 5 → (2)

Subtract (1) from (2) term by term to eliminate y

2x - x + (- 5) - 1 = y - y + (- 5) - (- 3) , that is

x - 6 = - 2 ( add 6 to both sides )

x = 4

Substitute x = 4 into either of the 2 equations and solve for y

Substituting into (1)

4 + 1 = y - 3

5 = y - 3 ( add 3 to both sides )

8 = y